KEMAMPUAN ARRESTER SEBAGAI PENGAMAN TRANSFORMATOR - Wirawan, Habib Yogi; Al-Amin, M. Saleh; Emidiana, Emidiana (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2021)
ABSTRACT Electrical interference at the substation might be caused by several internal and external factors. The interference that were often had was the interference caused by nature, namely lightning which caused overvoltage. The substation was an important place because it supplied the electrical energy to consumers who need to be protected from lightning interference. Some types of interferences in the power line were not completely avoidable but could be minimized or minimized by preventing interference electrical device failure. Lighting arrester was a means of protection for electrical equipment against lightning surges. For good protection the arrester should be located as close to the transformer as possible. The maximum distance for the installation of the arrester had to determine so that it could become a barrier for the installation of the arrester to protected the equipment. This research focused only on one arraster 3 bay trafo and one 60 MVA power transformer, and this study aimed to calculate the maximum distance of the arrester and the ability of the arrester to protected the transformer. Based on the calculation of the maximum distance between the placement of the arrester and the transformer at the keramasan substation, the maximum distance was 28 meters. And lightning arresters were able to protect the trafo because the maximum voltage that occured was only 646 kV where this voltage value was still below the TID of the equipment.